Aromatic diazo and azo compounds LXIV. New amino compounds and new azo dyes based on naphto[2,1-d]oxazole - Mužík, Ferdinand (University of Pardubice, 2011)
The paper is focused on innovation of a chemical process leading to new amino compounds of structural formula I and their application to preparation of new azo dyes II. The procedure of preparation of the key derivative is presented. This derivative is aminonaphthoxazoledisulfonic acid III, which is used in syntheses of a number of azo dyes belonging to various technological and application categories. In this way, a chemically new class of azo dyes, containing the naphtho[2,1-d]oxazole skeleton in their molecules, was established.